The efficacy and safety of annulus fibrosus suture as adjuvant therapy for lumbar disc herniation: a systematic review and meta-analysis - Ouyang, Wensi; Guo, Guimei; Sun, Yu; Jiang, Haobo; Chen, Long; Yang, Shaofeng (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveLumbar disc herniation (LDH) has demonstrated a rising prevalence in contemporary clinical practice, significantly compromising patients’ daily lives and potentially necessitating surgical intervention. While annulus fibrosus suture (AFS) techniques are increasingly incorporated into surgical protocols, current evidence remains inconclusive regarding their definitive clinical advantages.MethodsWe performed a comprehensive search of eight databases from inception to September 2025 to identify published articles on AFS for LDH. Outcome measures encompassed operative time, incision length, blood loss, length of stay (LOS), visual analog scale (VAS) score, Japanese Orthopedic Association (JOA) score, Oswestry disability index (ODI) score, disc height, recurrence, and complication. The quality of the studies was analyzed using the RoB-2 and ROBINS-I tools. Statistical analyses were performed using RevMan 5.4 software and Stata 17 software. The GRADE approach was used to evaluate the certainty of evidence for outcomes.ResultsA total of 58 studies encompassing 5,765 patients diagnosed with LDH. The control group had shorter operative time (MD = 4.85, 95% CI: 2.79 to 6.92, P < 0.00001) compared to the AFS group. There were no differences in terms of incision length, blood loss, LOS, JOA score, ODI score, and complication between the techniques. AFS group demonstrated a significant benefit over control group in terms of VAS score (MD = −0.24, 95% CI: −0.33 to −0.14, P < 0.00001), disc height (SMD = 1.36, 95% CI: 0.73 to 2.00, P < 0.0001), and recurrence (RR = 0.34, 95% CI: 0.27 to 0.42, P < 0.00001). The results of subgroup analysis showed that different study types and different follow-up times were a source of heterogeneity. The quality of evidence for outcome measures ranges from very low to moderate.ConclusionCurrent evidence suggests that AFS therapy may be advantageous in improving clinical symptoms and may reduce postoperative recurrence. Due to limited data and low quality of evidence, additional large-scale, multicenter trials are needed to verify and strengthen these findings.